Bempedoic acid: what prospective uses?. (26th April 2023) - Jacomelli, Ilaria; Monzo, Luca; Panattoni, Germana; Lanzillo, Chiara; Rebecchi, Marco; Calò, Leonardo
Abstract: There is still the need to lower LDL-c, although the use of statins, ezetimibe and proprotein convertase subtilisin/kexin type 9. Patients with atherosclerotic cardiovascular disease and/or familial hypercholesterolaemia are treated with statins at maximum tolerated dose, with or without further lipid-lowering drugs, but very often, we can't reach the goal, so bempedoic acid treatment lead to a significant reduction in low-density lipoprotein cholesterol, in different groups of patients, with a favourable safety profile.